Strategic Framework For Customer Relationship Management (CRM) Implementation By Oman Telecommunication Company (OMANTEL) - Ajham Al-Shahri, Amal Ahmed (2005)
The study is inspired by many theoretical viewpoints covering various related topics of CRM strategy. Omantel Group is chosen as a qualitative case and it was chosen as a field study to find out whether Omantel Group is applying any CRM strategy or thinking of that.